Investigation of structural, magnetic and ferroelectric properties of (1-x) Bi0.5Na0.5TiO3 – xBaFe12O19 and (1-x) Bi0.5Na0.5TiO3 – xBaFe11.5Co0.5O19 composites - Garg, Himanshi (My University, 2019)
Lead free (1-x) Bi0.5Na0.5TiO3 – xBaFe12O19 and (1-x) Bi0.5Na0.5TiO3 – xBaFe11.5Co0.5O19 ceramic composites are prepared by solid state ceramic route with different weight ratio x = 0.075, 0.15, 0.225, and 0.30. Structural and magnetic properties were investigated with X-ray diffraction, scanning electron microscope and vibrating sample magnetometers. XRD confirms two distinct phases for BNT-BaM composites without any intermediate phase formation. The reduction in the average crystallite size from 54 to 46 nm for composites confirms the pinning effect by BaM. SEM micrographs endorse two different morphologies in the composites. The average grain size was increased with cobalt substitution in BaM composites. Magnetization found to increase with BaM fraction due to its magnetic nature.The coercivity of 0.925 BNT composite shows the highest value around 1.8 kOe. Saturation polarization of 70BNT-30BaCoM composite show higher value (0.496μC/cm2).
Keywords: Multiferroic; Bismuth Sodium titanate; Barium Hexaferrite; Barium Cobalt ferrite